PEMBELAJARAN HADIS PADA ANAK USIA DINI DALAM MENGEMBANGKAN NILAI AGAMA DAN MORAL - Oktaviah Amaliah; Ida Rianty (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study is based on the fact that nowadays many children's behaviors are influenced by things that should not be done by children their age, such as using bad language and hate speech, and committing violence against friends. Early childhood is influenced by electronic media which is currently very easy to obtain compared to moral education that should be instilled in the development period of early childhood. So it is necessary to educate children's religious and moral values ​​from an early age through learning the hadith. This study was conducted to determine how learning the hadith can develop children's religious and moral values. The method used is qualitative with a descriptive research type, observation data collection techniques, interviews and documentation and data analysis with the Miles and Huberman model. The results obtained are that learning the hadith in children is carried out every day after the child has finished reading the surahs and short prayers. This activity is routinely carried out so that children continue to remember the hadith they have memorized. Based on observations, it can be seen that children have memorized the hadith about eating, cleanliness and the prohibition of anger, then children practice it by reciting the hadith when there are friends who eat while standing, there are also those who litter and get angry with other friends. Thus, based on this, the development of children's religious and moral values ​​shows that children already have good behavior and know about bad behavior through routine learning of the hadith.